Tantangan Disharmonisasi Regulasi dalam Pengelolaan Tanah Kas Desa - Dimas Bayu Anggoro; Zuber Zuber; Anita Kamiliah; Aji Mulyana (Lembaga Pengembangan Kinerja Dosen, 2025)
Disharmony Between Village Regulations and the Basic Agrarian Law in the Management of Village-Owned Land: A Normative Juridical Review. Village Treasury Land (Tanah Kas Desa/TKD) is a strategic asset governed by both Village Regulations and the Basic Agrarian Law. In practice, overlapping regulations and utilization of TKD have been identified, leading to administrative and legal conflicts among village governments, communities, and third parties. This study aims to examine the disharmony of norms between Village Regulations and the Basic Agrarian Law, and to formulate a legal harmonization model that can strengthen legal certainty and justice in the management of TKD. The research method used is normative juridical, with a statutory and conceptual approach. The findings reveal inconsistencies between several Village Regulations and the normative provisions of Law Number 5 of 1960 concerning the Basic Agrarian Principles, particularly regarding the legal status of TKD, licensing for its use, and authority in its management. This condition underscores the urgency of regulatory harmonization through strengthening legal guidance, supervision of village asset governance, and aligning the substance of village regulations with higher-level legislation. It is recommended that local governments enhance guidance and oversight in the formulation of Village Regulations, as well as promote the synchronization of agrarian regulations to ensure that TKD management complies with national legal standards